A Contradiction of Corporate Social Responsibility in Moderating Tax Avoidance - Hilda Mary; Nila Pratiwi; Anatia Agusti (Information Technology and Science (ITScience), 2022)
This study will look at tax avoidance through CSR as a moderating variable along with capital intensity, institutional ownership, and firm size. The independent variables are capital intensity, institutional ownership, and firm size, while the dependent variable is tax avoidance. As well as CSR as a moderating variable. This study focused on manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2021. In this study, the sample was determined using the purposive sampling method, which yielded a sample of 44 companies from 195 populations. Eviews 10 was used to analyze the research data using panel data analysis techniques. According to the findings of the study, Capital Intensity has a partial effect on Tax Avoidance, Institutional Ownership has a partial significant effect on Tax Avoidance, and Company Size has no significant effect on Tax Avoidance. Tax avoidance is influenced by capital intensity and institutional ownership, which are moderated by CSR. While CSR has no effect on tax avoidance, company size does. It is hoped that this study will assist manufacturers listed on the Indonesia Stock Exchange in determining tax avoidance by taking into account the factors that have a significant effect on tax avoidance, such as the effect of capital intensity, institutional ownership, and company size, as well as CSR as a moderating variable.